Effectiveness of Line Chatbot to find procedure code (ICD-9) guidelines for medical coders at Thammasat University Hospital - Wongfung, Kamonwan (Thammasat University Hospital Journal Online, 2023)
Background: Thammasat University Hospital is a 4.0 hospital aimed at being an organization of the future for the people. The researcher is therefore interested in applying information technology using the LINE application to help find criteria for assigning procedure codes (International Classification of Diseases version 9: ICD-9) and to develop its learning. A fast, comprehensive method will systematically help develop coders’ skills, resulting in the quality of procedure coding at the same standard. Objective: To study the efficiency of the current situation and the need for using media or equipment in searching for procedure codes. To develop and study the results of Line Chatbot with procedure code criteria for medical coders. (It also evaluates code giving, the accuracy of code giving, and satisfaction with using Line Chatbot). Methods: Phase 1: Study the situation problem and the need for using media or equipment in searching for criteria for giving procedures. Phase 2: Create a Line Chatbot for criteria for giving procedures. Phase 3: Test it with medical coders of Medical records of 11 patients at Thammasat University Hospital, then complete a test and satisfaction assessment, Phase 4: Evaluate the process. Result: The duration and accuracy scores obtained from the test before and after using the Line Chatbot were statistically different at 0.05. After using Line Chatbot, the time taken to complete the test decreased. It also resulted in a higher accuracy score than didn’t use Line chatbots. The overall evaluation of satisfaction with Line Chatbot and the criteria for assigning procedure codes was at the highest level ( =4.81, SD=0.261). Conclusion: Using the Line Chatbot for giving procedure codes makes the work of medical coders for patient medical records at Thammasat University Hospital more convenient, faster, and more accurate. It can be used as a tool along with actual work. When the code is given more quickly and accurately, it will result in the ability to send information for reimbursement quickly and reduce errors in sending the reimbursement related to procedure codes.